2007
DOI: 10.1159/000106478
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Age-Related Hearing Impairment: Contributing Environmental and Genetic Factors

Abstract: Age-related hearing impairment (ARHI) is the most common sensory impairment seen in the elderly. It is a complex disorder, with both environmental as well as genetic factors contributing to the impairment. The involvement of several environmental factors has been partially elucidated. A first step towards the identification of the genetic factors has been made, which will result in the identification of susceptibility genes, and will provide possible targets for the future treatment and/or prevention of ARHI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
206
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(214 citation statements)
references
References 259 publications
2
206
1
5
Order By: Relevance
“…8 In addition, several association studies based on a candidate gene approach and two genome-wide association studies (GWAS) 8,9 have been conducted. Early candidate gene-based association studies are reviewed by Van Eyken et al 10 Recently, based on a candidate gene approach, we reported associations between ARHI and variants in GRHL2, 11 encoding a transcription factor that is also involved in monogenic hearing loss. In addition, based on a pooling GWAS, we reported association with variants in the glutamate receptor-7 gene (GRM7), 9 encoding a metabotropic glutamate receptor assumed to modulate hair cell excitability and synaptic efficacy.…”
Section: Introductionmentioning
confidence: 84%
“…8 In addition, several association studies based on a candidate gene approach and two genome-wide association studies (GWAS) 8,9 have been conducted. Early candidate gene-based association studies are reviewed by Van Eyken et al 10 Recently, based on a candidate gene approach, we reported associations between ARHI and variants in GRHL2, 11 encoding a transcription factor that is also involved in monogenic hearing loss. In addition, based on a pooling GWAS, we reported association with variants in the glutamate receptor-7 gene (GRM7), 9 encoding a metabotropic glutamate receptor assumed to modulate hair cell excitability and synaptic efficacy.…”
Section: Introductionmentioning
confidence: 84%
“…Diese sensorineurale symmetrische Altersschwerhörigkeit ist deutlich im Hochtonfrequenzbereich ausgeprägt [5,12]. Die altersbedingte Hörminderung kann entweder auf lebenslange exogene und endogene Einflüsse sowie auf genetische Faktoren zurückzuführen sein [7,13,14]. Die Lärmexposition (Intensität und Dauer des Lärms) tritt in der Literatur als prädisponierender exogener Risikofaktor auf [5].…”
Section: Hintergrundunclassified
“…Die Lärmexposition (Intensität und Dauer des Lärms) tritt in der Literatur als prädisponierender exogener Risikofaktor auf [5]. Zu den negativen Einflüssen zählen zudem Ototoxine (ohrschädigende Substanzen), Rauchen [12], Infektionen, Schlaganfall [6,14], Hypertonie, Herz-Kreislauf-Erkrankungen, Diabetes und Durchblutungsstörungen [7,13]. Das Potenzial der Komorbiditäten als Risikofaktoren für Altersschwerhö-rigkeit wird in der Forschung kontrovers diskutiert.…”
Section: Hintergrundunclassified
“…The onset of presbyacusis is not consistent among individuals. There are many factors which hasten the onset of presbyacusislike nutrition, lifestyle, environment [4] and occupational hazards, infection and illness, drug intake, hereditary etc.…”
Section: Discussionmentioning
confidence: 99%